2021
DOI: 10.1016/j.ejrad.2021.109583
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center study of COVID-19 patient prognosis using deep learning-based CT image analysis and electronic health records

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Our study also indicated that some studies developed new networks based on existing widely used networks such as AlexNet, U-Net, ResNet, VGG, and GoogLeNet [13,42,43]. Since GAN was proposed, DCGAN [44], WGAN [45], CycleGAN [21], BEGAN [46], and BigBiGAN [47] were optimised for domain adaptation, data augmentation, and imageto-image translation.…”
Section: Discussionmentioning
confidence: 76%
“…Our study also indicated that some studies developed new networks based on existing widely used networks such as AlexNet, U-Net, ResNet, VGG, and GoogLeNet [13,42,43]. Since GAN was proposed, DCGAN [44], WGAN [45], CycleGAN [21], BEGAN [46], and BigBiGAN [47] were optimised for domain adaptation, data augmentation, and imageto-image translation.…”
Section: Discussionmentioning
confidence: 76%
“…Artificial intelligence (AI) has also contributed to the detection of lung changes characteristic of COVID during the pandemic [19,20,42,43]. CAD programs can define the presence of SARS-CoV-2 infection and evaluate the severeness of the disease by analyzing the characteristic opacity patterns and their volume inside the lungs both in CT and X-ray images and, thus, help doctors to diagnose and properly treat COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Data mining algorithms have only been used to discover symptom patterns in COVID-19 patients [ 52 ] as well as to make predictions about COVID-19 patient severity [ 2 , [7] , [8] , [9] ] and recovery [ 53 ]. The MLP algorithm classified the severe patients with a precision (96.5%), similar to XGBoost [ 9 ] and other multipurpose algorithms [ 7 ], but with the advantage of using laboratory tests.…”
Section: Discussionmentioning
confidence: 99%
“…ML algorithms are just beginning to be investigated as prognostic tools. ML-driven predictions of COVID-19 outcomes are based on clinical data and largely radiological features extracted from X-ray computed tomography (CT) [ 2 , [7] , [8] , [9] ]. However, CT scan images are time consuming, weakly correlated with initial disease severity [ 10 ] and unable to detect small infected lung regions.…”
Section: Introductionmentioning
confidence: 99%